PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP KINERJA PERUSAHAAN - Widyaningrum, Diptya; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
This study aims to examine the impact of the environmental, social, and governance (ESG) disclosure and each of its pillar on the firm performance using EBIT as the proxy. Sustainability report, which is a form of firm responsibility, can be a company strategy in attracting the attention of stakeholders. This study incorporates dependent variable (environmental disclosure, social disclosure, governance disclosure, and ESG disclosure), independent variable (firm perfomance), and control variables (leverage and listed years).The population in this study comprises non-financial companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling was carried out through purposive sampling, resulting in a total of 186 research samples.  The analysis method employed in this study is panel regression analysis.The findings of this study indicate that ESG disclosure as measured through the ESG score has a positive influence on firm performance Meanwhile, when measured individually, social disclosure and governance disclosure also has a positive influence on firm performance, but environmental disclosure does not have an influence on firm performance.